The contributing factors of volunteer satisfaction and intent to remain among community service volunteers in organizing events course / Hazlin Hasan … [et al.] - Hasan, Hazlin; Abu Bakar, Suwaibah; Jais, Mohammad; Ab Halim, Roslilee; Mohd Mokhtar, Noorsuraya (2012)
Malaysians are showing more interest in involving themselves in community service projects recently. Both non governmental as well as private organizations have started to reach more to the needy through various community projects. Locally or internationally, the community service projects usually depend heavily on volunteers. They enable event managers to add and to expand the quantity and diversity of services without exhausting the budget. They are considered a valuable commodity as research has suggested that the available pool of volunteers may be declining due to various reasons which include the volunteer satisfaction. As such. this study examined the satisfaction level of Office Management diploma program students who act as volunteers in community service projects undertaken by them as part of their course requirements. The primary purpose of this research was to investigate the volunteers' satisfaction level and factors that contributed to volunteers' intent to remain in community service projects. A set of questionnaire was distributed to five groups of students taking the Organizing Events (OMT290) course that organized community service as their projects. The data was analyzed for descriptive and inferential statistics using the SPSS Version 20. The findings identified the factors that (highest dimension) lead to volunteer satisfaction and their intent to remain in community service. It was found that the respondents showed high level of satisfaction with the community service experience. Further research on the relationship on volunteer satisfaction and intent to remain would be conducted to contribute to the body of knowledge.